Effect of Salt in Irrigation Water on Some Physical and Chemical Properties of Lettuce Plant and Soil - YAGMUR*, BÜLENT; AYDIN†, SENAY; OKUR, BÜLENT; COSKUN†, AYSEN (Asian Journal of Chemistry, 2009)
Knowledge of salt tolerance in vegetable plants is necessary to increaseproductivity and profitability of crop irrigated with saline waters. Thisresearch was carried out in Celal Bayar University, Alasehir vocationalschool glasshouse which is in Manisa, Alasehir located in the west partof Agean region. The purpose of the experiment is to determine salinityeffects on some chemical and physical properties of lettuce plant andsoil and some vegetative growth parameter of plant which is irrigatedwith water having different concentrations of salt (NaCl). The experimentwas established in a randomized block design with four replications.Salinity levels are in five levels as 0-4-8-12-16 dSm-1 EC. Dependingon increasing salt concentration in irrigation water, from the soil saturationextract values, especially Na+ from cations and Cl– from anionswhich are dominant compared to others (K+, Mg2+, SO42-, HCO3–) andalso increase of total soluble salt values have caused some negativenessin plant production. Different EC levels in irrigation water showed animportant effect on K+ and Na+ content of soil and only Na+ content ofplant. Highest values were generally obtained at 4 dSm-1 EC for lettuceplant vegetative growing parameters such as dry and fresh head weight,head length and leaf number per plant. However, the increase in saltcontent of water (> 4 dSm-1 EC) affected negatively these vegetativegrowing parameters.